Comparative Analysis of Modern Concepts of Information Warfare - R. S. Vykhodets; K. A. Pantserev (Евразийская интеграция: экономика, право, политика, 2022)
This study is devoted to the comparative analysis of the subject fields of the main modern concepts of information and psychological warfare.Aim. To identify the features of the subject fields of the main modern concepts of information and psychological warfare.Tasks. To analyze the main modern concepts of information and psychological warfare: information war, network war, network-centric war, mental warfare; determine their essential characteristics and identify the features of subject fields.Methods. During the research, both general scientific (analysis, synthesis, analogy) and special methods were by the authors in order to solve scientific problems: content analysis, comparative analysis, critical discourse analysis.Results. The study showed that the term “information  warfare” has appeared in  a  report commissioned by the US Department of Defense. Further, this concept was actively operated by American military experts involved in the development and planning of various types of military operations. The attitude to this term in scientific circles is ambiguous. In the scientific literature, one can find a large number of definitions explaining this phenomenon, which indicates the ongoing discussions in the scientific world about the sense of the “information war” as the phenomena.Often this term is replaced by the term “information and psychological warfare”, which should be understood as such a relationship between states in which one of the opposing parties, in order to expand its zone of influence and eliminate potential competitors, resorts to active covert influence on the information  sphere  of its opponent,  aimed at creating  conditions  for making  favorable decisions for one or the other state in military, political, economic and other fields.Conclusions. The authors come to the conclusion that the theory of information warfare should be considered as an area of scientific research aimed at understanding the use of advanced technologies in interstate confrontation which causes fundamental changes in the forms, principles and means of conflicts in the information age. Currently, the theory of information warfare has been differentiated and developed in a number of original concepts that focus on various aspects of confrontation in the information environment and the use of ICT in military confrontation.